Analisis Bahaya Area Kampus bagi Pihak Eksternal: Studi Kasus di sebuah Universitas Swasta - Billy Danuharjo Gani; I Nyoman Sutapa; Benedictus Rahardjo (Jurnal Titra, 2020)
This case study was done at a private university located in Surabaya. The aims of this study was to analyze the potential hazards and risks of workplace accidents. The university is preparing for the stage of the Occupational Health Safety Management System (SMK3). The Hazard Identification, Risk Assessment and Risk Control (HIRARC) method is adopted to detect activities on external parties and arrange for its control so that the potential for workplace accidents can be minimized. The design of HIRARC for external parties of university was 51 potenial hazards. This potential hazard has an extreme risk assessment value of 0% , high 24%, moderate 25% and low 51%. The proposed risk control for K3 induction such as guidebook and video safety induction. In addition, risk control is carried out by means of elimination, substitution, administration, and personal protective equipment.